Penyuluhan Anti-Aging Sebagai Bentuk Pengabdian Kepada Masyarakat di SMA Negeri 3 Singaraja, Buleleng - Rahasbistara, Made Rendra Wisnu; Ginitri, A. A. Bulan; Putra, Made Adit Darma; Antara, I Nyoman Adi Arta; Novitrianti, Anak Agung Istri Aiswarya (Abdimas Indonesian Journal, 2025)
Aging is a natural process experienced by every individual and influenced by both internal and external factors. External factors such as ultraviolet (UV) exposure, pollution, unhealthy lifestyle, and poor diet can accelerate premature aging. The impacts are not only visible on the skin but may also increase the risk of degenerative diseases and reduce the overall quality of life. The World Health Organization (WHO) stated that excessive UV exposure contributes to the rising incidence of skin cancer, premature skin aging, and other health problems (WHO, 2021). Therefore, education on the prevention of external aging factors, including skin protection from UV rays, the use of sunscreen, healthy lifestyle, regular exercise, and balanced nutrition, is essential to raise awareness among adolescents from an early age. This outreach activity focused on providing health education on the dangers of UV radiation and external aging factors as part of the Community Service Program (PkM) of the Faculty of Medicine, Mahasaraswati University, Denpasar. The program was conducted at SMA Negeri 3 Singaraja -Buleleng, involving students as active participants.